The Role of Product Quality in Influencing Consumer Decisions to Purchase Televisions in Way Jepara, East Lampung - Eka Parianti; Susi Sulastri; Diki Wahyudi (Journal of Research in Social Science and Humanities, 2024)
In line with the rapid advancements of the times, accompanied by the development of science andinformation technology, people are increasingly required to enhance their potential to understand and adaptto emerging technologies and changes in their respective fields. The need for accurate and fast informationservices has become essential for everyone. As a result, televisions have now become a basic need for many,as they cater to a person#39;s needs in various areas such as business, entertainment, and more. This hascontributed to the booming growth of the electronics trade, as the increasing demand from society makes iteasier for electronic stores, especially those selling televisions, to sell products from various brands.The electronic stores in the Way Jepara subdistrict of East Lampung sell a wide range of electronicproducts, including televisions. The brands of televisions that are most frequently purchased or favored bythe community include Panasonic, Sharp, and Goldstar. Meanwhile, other brands, such as those from China,are also popular among consumers, contributing to the stable monthly sales of televisions. However, there isa need to increase consumer trust to encourage more purchases or product selection.Therefore, in this study, the researcher formulates the problem: quot;Is there a relationship between productquality and consumer decisions in purchasing televisions in the Way Jepara subdistrict of East Lampung?quot;The purpose of this study is to identify and analyze whether there is a relationship between product qualityand consumer purchasing decisions for televisions in the Way Jepara subdistrict of East Lampung.The data collection techniques used in this study include field research, literature research, andquestionnaires. The population of this study consists of individuals or consumers who have purchasedtelevisions in the Way Jepara subdistrict of East Lampung. This study uses the independent variable ofproduct quality (x) and the dependent variable of consumer decision (y).The analytical technique used in this research is the Spearman Rank correlation. Based on the analysisconducted, it was found that the calculated rho value is greater than the table rho value, or 0.985 gt; 0.364.This means that the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected,indicating that there is a relationship between product quality and consumer decisions in purchasingtelevisions in the Way Jepara subdistrict of East Lampung, amounting to 98%. Meanwhile, the remaining2% is influenced by other factors such as product price and others.